The concept of forgiveness as soul therapy: Healing of inner wounds, child in the Qur’an - Fangesty, Maolidya Asri Siwi; Fathurrahman, Asep Ahmad (UIN Sunan Gunung Djati Bandung, 2025)
This study analyzes the concept of forgiveness in the Qur'an through the terms 'afw, ṣafh, and gufran, exploring their semantic, theological, and contextual meanings. It integrates this Qur'anic understanding with the psychological concept of the wounded inner child, showing forgiveness as both a moral duty and a spiritual healing process for emotional wounds and past trauma. Using qualitative methods, the research reveals forgiveness in Islam as a multidimensional mechanism involving emotional regulation, relationship transformation, and spiritual growth. It highlights how God's grace restores self-worth and inner peace. This study bridges tafsir and psychology, offering new insights by integrating the inner child concept with Qur'anic forgiveness for practical psychological healing.